Uma pequena cidade, uma grande relação: Piraju (SP) e a importância do café - Pereira, Thiago Henrique Valério (2013)
The coffee was an important economic element to Brazil and to the state of São Paulo, especially in the late nineteenth and early twentieth century. With this enabled the emergence and spread of techniques such as railways, and the appearance of small nuclei, what later became consolidated as cities. In this context, emerged the municipality of Piraju in the São Paulo State, our spatial snip. The coffee economy was their main activity, possible extension of the arrival Sorocabana, in 1908 and the involvement of local politicians in public life in São Paulo. After this phase and after crises ace, as the of 1929, that destabilized the economy, Piraju still continued in these crops. The coffee has created a bond with this small cities, because currently is an activity performed in Piraju, now with new management techniques and of market, which led to having a broad highlighted with awards at national and international levels. We adopt the method regressive-progressive of Lefebvre to understand the diachronic and synchronic time / space relationship of coffee and Piraju, compare the phenomena of the past and present, just as one may respond to another. Withal, we conclude that the district created an identity with coffee, having interference in the culture, in politics and the economy.